IMPLEMENTASI PENGGUNAAN BAHASA JAWA KRAMA INGGIL DALAM MENANAMKAN NILAI KESOPANAN DI SD NEGERI PURWOYOSO 04 SEMARANG - Devita Ummul Musyarofah; Yuni Nur Cahyani; Rezza Sari Febriani; Juninta Natasya Rahmawati; Intan Nur Aini; Galih Mahardika Christian Putra (Jurnal Genta Mulia, 2025)
This study aims to determine the implementation of the use of Javanese Krama Inggil in instilling politeness values ​​in Purwoyoso 04 Elementary School, Semarang. The background of this study is based on the phenomenon of the decreasing use of Javanese Krama Inggil among students, which has an impact on low awareness of manners or etiquette in communication. This study uses a descriptive qualitative methodology, data collection through questionnaires, interviews, documentation, and observation. The results of the study indicate that the application of Javanese Krama Inggil can influence students' character, especially in terms of politeness. However, there are a number of obstacles in its realization, which come from the interests and learning styles of the children themselves as well as external factors such as family, school, and society. To re-increase awareness of the importance of using Javanese Krama Inggil as an effort to preserve culture and instill noble ideals in basic education, teachers, parents, and the wider community must work together.